Multiscale Modeling of Pollutant Uptake by Mangroves - Nguyen, H; Richter, O (The International Journal of Multiphysics, 2016)
Models for pollutant uptake by mangrove plants are developed at different scales and applied to the environmental fate of a pollutant in an estuary. Employing cohesion-tension theory, a 3-dimensional model of water and substance flow in young mangrove trees is set up in form of porous media equations. Water transport is conceived as a continuous hydraulic process driven by canopy transpiration. State variables are water potential and pollutant concentrations in the soil, roots, xylem, core and canopy. At catchment scale, the mangrove forest is conceived as a flow reactor. Up-scaled models are derived from a 3-dimensional single plant model by fitting a compartment model in form of ordinary differential equations to data obtained by spatial integration over the domains of the 3-dimensional model. These equations are imbedded as reaction terms into the shallow water equations for riverine transport. The model is applied to the dispersal of pollutants in an estuary.